2019
DOI: 10.15835/nsb11410485
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Aqueous Leaf Extract of Moringa oleifera on Reproductive Function Following Cadmium Chloride Induced Oxidative Stress in Male Wistar Rats

Abstract: Cadmium disrupts the blood-testes barrier, interferes with various antioxidant levels thus enhancing lipid peroxidation and ultimately leading to apoptosis and necrosis of testicular tissue. Moringa oleifera is a medicinal plant and a rich source of essential phytochemicals possessing antioxidant properties. The effect of aqueous leaf extract of M. oleifera on reproductive function following cadmium chloride induced oxidative stress in male Wistar rats was investigated. Forty adult male Wistar rats were assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Ododo et al in their study proved that exposure to CdCl 2 disrupts the arrangement of spermatogenesis cell lineage and decreases the spermatogenesis and Leydig cells in seminiferous tubules, seminiferous tubule diameter and germinal epithelial height and destroys tunica albuginea. (Ododo et al, 2019). This study showed that prescribing of the Feijoa extract to CdCl 2 -received rats can increase the number of spermatogonia, Leydig and Sertoli cells as well as increase the germinal epithelial thickness and seminiferous tubules diameter.…”
Section: Discussionmentioning
confidence: 70%
“…Ododo et al in their study proved that exposure to CdCl 2 disrupts the arrangement of spermatogenesis cell lineage and decreases the spermatogenesis and Leydig cells in seminiferous tubules, seminiferous tubule diameter and germinal epithelial height and destroys tunica albuginea. (Ododo et al, 2019). This study showed that prescribing of the Feijoa extract to CdCl 2 -received rats can increase the number of spermatogonia, Leydig and Sertoli cells as well as increase the germinal epithelial thickness and seminiferous tubules diameter.…”
Section: Discussionmentioning
confidence: 70%
“…Paracetamol has been established as a pain relief medication of great efficacy 28 , yet it has a number of negative effects on the test is 8 . M. oleifera has numerous benefits to the health of humans 29 , and has been demonstrated to reduce the impact of some testicular toxins 30 . The focus of this study is to explore the ameliorative potential of aqueous leaf extract of Moringa oleifera on paracetamol induced testicular toxicity using Sprague-Dawley rats.…”
mentioning
confidence: 99%